1987
DOI: 10.3109/02713688709034835
|View full text |Cite
|
Sign up to set email alerts
|

The effect of beta irradiation on monkey Tenon's capsule fibroblasts in tissue culture

Abstract: Fibroblast proliferation with subsequent bleb scarring is a major cause of filtering surgery failure. To investigate possible antiproliferative effects of beta radiation, owl monkey Tenon's capsule fibroblasts in tissue culture were irradiated to doses of 30, 100, 300, 1,000, and 3,000 rads with a linear accelerator and to doses of 95,285, and 950 rads with a Strontium-90 applicator. The irradiated cell proliferation expressed as the percentage of the non-irradiated control growth on the third and seventh days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The potential benefit of beta decay in ophthalmology was predicted in animal models in 1987, when cultured monkey ocular fibroblasts were shown to undergo rapidly reduced proliferation following exposure in vitro. 14 Since then, there have been reports of radiation used as an adjunctive treatment for pterygium and glaucoma filtration surgery. 10 , 15…”
Section: Radiation and Neovascular Amdmentioning
confidence: 99%
“…The potential benefit of beta decay in ophthalmology was predicted in animal models in 1987, when cultured monkey ocular fibroblasts were shown to undergo rapidly reduced proliferation following exposure in vitro. 14 Since then, there have been reports of radiation used as an adjunctive treatment for pterygium and glaucoma filtration surgery. 10 , 15…”
Section: Radiation and Neovascular Amdmentioning
confidence: 99%
“…The first published report was by Nevarez et al , who reported that over a 7 day period, single doses of β radiation significantly inhibited monkey fibroblast proliferation relative to unirradiated control cells 14. Khaw et al subsequently described a similar effect in human ocular fibroblasts over a 14 day period 15.…”
mentioning
confidence: 99%